2014
DOI: 10.1128/jb.01974-14
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Comparison of the Burkholderia pseudomallei, Burkholderia thailandensis, and Burkholderia mallei Quorum-Sensing Regulons

Abstract: c Burkholderia pseudomallei, Burkholderia thailandensis, and Burkholderia mallei (the Bptm group) are close relatives with very different lifestyles: B. pseudomallei is an opportunistic pathogen, B. thailandensis is a nonpathogenic saprophyte, and B. mallei is a host-restricted pathogen. The acyl-homoserine lactone quorum-sensing (QS) systems of these three species show a high level of conservation. We used transcriptome sequencing (RNA-seq) to define the quorum-sensing regulon in each species, and we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…Recent RNA-seq studies by Greenberg and coworkers have allowed identification of a core set of genes that is QS-activated in the Pseudomallei group pathogens, which include B. thailandensis, B. pseudomallei, and B. mallei (19,22). Because of the importance of LTTRs in regulating secondary metabolite production in other Proteobacteria, we searched the RNA-seq datasets for transcriptional regulators that were common to all three strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent RNA-seq studies by Greenberg and coworkers have allowed identification of a core set of genes that is QS-activated in the Pseudomallei group pathogens, which include B. thailandensis, B. pseudomallei, and B. mallei (19,22). Because of the importance of LTTRs in regulating secondary metabolite production in other Proteobacteria, we searched the RNA-seq datasets for transcriptional regulators that were common to all three strains.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, MvfR has advanced to a target for the development of strategies to combat P. aeruginosa infections. Orthologs of scmR are also abundantly expressed in B. pseudomallei and B. mallei as a function of QS (22). It will be interesting to examine the roles of scmR in virulence factor production in these strains and to explore whether interfering with its function can lead to effective therapies against Pseudomallei group pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Each study focused on a different organism, and the growth conditions also differed; hence, the number of genes that were differentially regulated in response to QS processes varied. In recent studies, the QS regulons represented up to 6.2% of the coding sequences in the P. aeruginosa genome (for lasI and lasR and for rhlI and rhlR) (58), up to 8.1% of the coding sequences in the Yersinia pestis genome (59), up to 8.0% coding sequences in the B. thailandensis genome (28), 0.8% of the coding sequences in the B. mallei genome, 3.6% coding sequences in the B. pseudomallei genome (30), and between 4.9 and 7.3% of the coding sequences in the in S. fredii NGR234 genome (40). We observed that 11.5% of all genes were differentially regulated by the three BGPG1 QS systems, and it was recently reported that up to 19.6% of the BGR1 genes were regulated in a QS-dependent manner in a tofI mutant (34).…”
Section: Global Pattern Of Qs-dependent Gene Expression In Bgpg1mentioning
confidence: 99%
“…Additionally, the phenotypes of the wild-type and mutant strains were comparatively studied, and a common set of orthologous QS-regulated genes was identified in B. glumae PG1 and the recently studied model organisms from the Bptm group (28,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation